Synthesis of Self-Assembled Porphyrin Nanoparticle Photosensitizers - Wang, Dong; Niu, Lijuan; Qiao, Zeng-Ying; Cheng, Dong-Bing; Wang, Jiefei; Zhong, Yong; Bai, Feng; Wang, Hao; Fan, Hongyou (ACS nano, 2018)
The use of nanoparticles as a potential building block for photosensitizers has recently become a focus of interest in the field of photocatalysis and photodynamic therapy. Porphyrins and their derivatives are effective photosensitizers due to extended π-conjugated electronic structure, high molar absorption from visible to near-infrared spectrum, and high singlet oxygen quantum yields as well as chemical versatility. In this paper, we report a synthesis of self-assembled porphyrin nanoparticle photosensitizers using zinc meso-tetra(4-pyridyl)porphyrin (ZnTPyP) through a confined noncovalent self-assembly process. Scanning electron microscopy reveals formation of monodisperse cubic nanoparticles. UV–vis characterizations reveal that optical absorption of the nanoparticles exhibits a red shift due to noncovalent self-assembly of porphyrins, which not only effectively increase intensity of light absorption but also extend light absorption broadly covering visible light for enhanced photodynamic therapy. Electron spin-resonance spectroscopy (ESR) studies show the resultant porphyrin nanoparticles release a high yield of singlet oxygen. Nitric oxide (NO) coordinates to central metal Zn ions to form stabilized ZnTPyP@NO nanoparticles. We show that under light irradiation ZnTPyP@NO nanoparticles release highly reactive peroxynitrite molecules that exhibit enhanced antibacterial photodynamic therapy (APDT) activity. The ease of the synthesis of self-assembled porphyrin nanoparticles and light-triggered release of highly reactive moieties represent a completely different photosensitizer system for APDT application.